Tax Burden on Rubber, Coconut and Pineapple Smallholders in Johore 1 - Hussein, Mohammed Ariff (1978)
The study examines whether taxes levied on rubber, coconut, and pineapple smallholders in 1975 are a major cause for smallholder low income. ' Results of the study show that tax burden on the smallholder is substantial, particularly that on rubber smallholders. The average rubber smallholder pays about one-fourth to onethird of his income in taxes. However, the scope for incrfasing income through changes in the tax structure is limited. Such changes should be coupled with programmes aimed at increasing farm productivity and size of holding.